2017
DOI: 10.17221/65/2016-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Identification and antibiotic resistance profiling of bacterial isolates from septicaemic soft-shelled turtles (Pelodiscus sinensis)

Abstract: ABSTRACT:The present study sought to identify pathogens associated with septicaemia in the Chinese softshelled turtle (Pelodiscus sinensis) and to characterise antibiotic resistance in these pathogens. Twenty-three isolates recovered from the livers of diseased soft-shelled turtles were genetically identified as Aeromonas hydrophila (n = 8), A. veronii (n = 3), Citrobacter freundii (n = 4), Morganella morganii (n = 3), Edwardsiella tarda (n = 2), Wohlfahrtiimonas chitiniclastica (n = 1), Chryseobacterium sp. (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 38 publications
2
23
0
2
Order By: Relevance
“…(Schmidt et al 2001;Deng et al 2015). In a recent study, the prevalence of tetA (54Á55%) was observed in aeromonads isolated from soft-shelled turtles (Pelodiscus sinensis) (Chung et al 2017). The presence of tetA, tetB and tetE genes were frequently reported in Aeromonas isolates (Verner-Jeffreys et al 2009;Dobiasova et al 2014).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…(Schmidt et al 2001;Deng et al 2015). In a recent study, the prevalence of tetA (54Á55%) was observed in aeromonads isolated from soft-shelled turtles (Pelodiscus sinensis) (Chung et al 2017). The presence of tetA, tetB and tetE genes were frequently reported in Aeromonas isolates (Verner-Jeffreys et al 2009;Dobiasova et al 2014).…”
Section: Resultsmentioning
confidence: 97%
“…The PCR products were sequenced and examined by the blast option in the GenBank database (Chung et al . ).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…In this study, none of the isolates harboured extended spectrum b-lactamase (ESBL) (blaTEM, blaSHV and blaCTX-M) genes although the isolates were phenotypically resistant to b-lactams. The ESBL genes have been detected from diseased fish, shrimp, turtles and other aquatic animals which indicates the higher prevalence of ESBL genes in clinical strains than environmental samples (Deng et al 2015;Chung et al 2017;Wimalasena et al 2017).…”
Section: Detection Of Antimicrobial Resistance Genesmentioning
confidence: 99%
“…Aeromonas and Pseudomonas spp. have been isolated from turtles with pneumonia, and many other infections in turtles with bacterial aetiologies have been described (McArthur 2004;Kohler 2006;Hernandez-Divers et al 2009;Chen et al 2013;Chung et al 2017).…”
mentioning
confidence: 99%